Report on the 12th International Conference in “Humanistic Ecology” Series: “The Church towards Ecological Crisis. On the 30th Anniversary of Polish Bishops’ Pastoral Letter on Environmental Protection” (Warsaw, 15 May 2019) - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2020)
The summary is not available.